Pneumopatia por micobacteria não tuberculosa em um hospital universitário na cidade de Belém Pará - BRANDÃO, Elton dos Anjos (2023)
Introduction: Non-tuberculous mycobacteria (NTM) pneumopathy is a disease which has achieved great importance, being caused by bacteria species belonging to the Mycobacterium genera. It occurs mainly in individuals who have a predisposing factor. Aims: To evaluate the prevalence of disease carriers, and to describe clinical, laboratorial and radiological features in these individuals, as well to explore the presence of risk factor in this population and describe the employed therapy and the patient's outcome. Methods: This is a descriptive transversal study of patients who received medical care on the pneumology department of a public reference University Hospital in Belém/Brazil with a non-tuberculous mycobacterium pneumopathy diagnosis, having sputum culture and undergone typing for mycobacterium, from 2002 through 2006. Patients diagnosed as having pulmonary tuberculosis and those whose medical records had been lost were excluded from the study. Assessed variates were: sociodemographic aspects, symptomatology, comorbid conditions, sputum test for mycobacterium, culture-typing for Non tuberculous mycobacteria, PPD, chest x-ray, employed therapy and patient's outcome. Results: From the 11 patients studied, the mean age was 59,27 ± 16,3 years-old, without sexual predominance. Cough was the main symptom found (91,0%), followed by thoracic pain (63,7%) and hemoptoic sputum (63,7%). Past medical history for tuberculosis was the most common predisposing factor (100,0%). The most frequently NTM found were: 45,4% (5/11) M. avium-intracellulare; 27,3% (3/11) M. abscessus; 18,2% (2/11) M. scrofulaceum e 9,1% (1/11) M. gordonae. The most important radiological findings were fibroatelectasis (45,5%) and pleural thickening fibrosis (36,4%). Ethambutol was the most commonly used drug in treatment (100%), followed by ofloxacin (63,7%). As for the patient's outcome, dropouts occurred in 50,0% of the cases and expectant management in 20,0%. Conclusion: There were no sexual predominance, the majority aged over 50 years old and had cough as the predominant symptom. M. avium-intracellulare was the most common mycobacterium species.